“You do not avoid sin by loquacity”: Ambiguous Truths in Kostas Ostrauskas’ Drama Eloiza ir Abelardas (Eloise and Abelard) - Pabarčienė, Reda (Colloquia, 2014)
In this article the author examines the historical contexts and intertexts of Kostas Ostrauskas’ play Eloiza ir Abelardas: Historia calamitatum (Eloise and Abelard: Historia calamitatum, written 1984–1985, published 1988). She identifies elements of the epistolary, scholastic, hagiographic, courtly, and feminist discourses that Ostrauskas uses in creating dialogue, action, conflict, and characters and in shaping the issues and motifs of his work. The article focuses especially on innovations of dialectics and logic in philosophy and theology of the first half of the twelfth century, relating these to Ostrauskas’ style of dramatic thinking and the intellectual nature of his oeuvre. This analysis of Eloiza ir Abelardas confirms the ambiguous relation of parody to cultural texts: they are diminished and mocked, but at the same time extended and adapted to raise questions about philosophical truth – to reveal its sacrum and profanum aspects and its rational and emotional modes of understanding, thus demonstrating how neither is able to bear witness to the truth.